Do Accounting Standards Matter for Productivity?. Issue 1 (16th October 2020) - Banker, Rajiv; Huang, Rong; Li, Yinghua; Zhao, Sha
Abstract : In this study, we examine whether productivity shifts when accounting standards change. Using mandatory International Financial Reporting Standards (IFRS) as a shock to the accounting regime, we examine the changes in country‐level productivity. We find that mandatory IFRS‐adopting countries experience significant increases in total factor productivity (TFP) and labor productivity. The post‐adoption productivity improvements are greater for countries without IFRS convergence. Further, TFP increases more for countries that experience a larger increase in industry comparability. Taken together, the evidence suggests that the new IFRS accounting regime increases economic productivity via improving information environments and facilitating internal firm decisions.